(untitled) (CIPEEX, 2025)
IT project management has become a core competency in a world where technology is the foundation of organizational competitiveness. Implementing systems, integrating new tools, and adapting to ever-changing technological environments require rigorous planning and effective control. This paper seeks to explore the project management practices applied to the IT sector, highlighting the importance of adequate management for the success of such projects. IT project management involves the use of specific methodologies, such as traditional (waterfall) and agile (Scrum, Kanban), which aim to organize and direct activities throughout the project life cycle. Traditional methodologies are characterized by more detailed and sequential planning, where all stages of the project are foreseen in advance. Agile methodologies, on the other hand, offer greater flexibility and adaptation, and are recommended for environments that demand rapid response to change. The method chosen depends on factors such as the complexity of the project, the resources available, and the organizational culture. In large-scale projects, where there is clarity about the objectives and the requirements are well defined, the waterfall method can be effective. In contrast, for projects that involve innovation or uncertainty, the agile approach allows for constant and incremental adjustments, making it easier to correct course. Case studies analyzed indicate that companies that adopt the agile approach report greater responsiveness to change and greater collaboration between teams. However, they also point out that a lack of rigorous planning can result in delays and overruns, demonstrating the importance of a balance between flexibility and control. IT project management requires a strategic and flexible approach, with the choice of the appropriate methodology for each situation. The combination of traditional and agile methods can bring considerable benefits, as long as it is well applied to the context of the project. Ultimately, the success of IT project management depends on the team’s ability to balance innovation with organization, ensuring the delivery of results on time and on budget.